Nutritive and Economic Value of Danish Fish Meal, Crayfish Dust Meal and Shrimp Waste Meal Inclusion in Broiler Diets - Ojewola, G.S.; Annah, S.I. (International Journal of Poultry Science, 2006)
Nutritional and economic evaluation of the dietary inclusion of Danish (imported) fish meal, crayfish dust meal and shrimp waste meal as animal protein sources in broiler ration was carried out using 144-day old broiler chicks in a completely randomized design experiment. This trial lasted seven weeks. The 144 – unsexed chicks of. Anak Strain were randomly allocated to 6 dietary treatments, with each having 2 replications of 12 chicks per replicate. The diets were designated as diets 1,2,3,4,5 and 6. Diets 1, 2 and 3 respectively had 6% Danish fish meal, crayfish dust meal and shrimp waste meal, while diets 4, 5 and 6 respectively contained 3% each of crayfish dust meal and shrimp waste meal. The birds were fed and watered ad libitum. Proximate analysis showed that the test ingredient (FM, CFDM and SWM) respectively had a crude protein content of 61.34%, 65.27% and 46.20%. The gross energy were 2614kcal/kg, 3625kcal/kg and 2982kcal/kg in that same order. The mean final body weight, daily weight gain, daily feed intake and feed - to -gain ratio showed no significant difference (P>0.05). Birds fed diet 4 gave the best (2.05) feed-to-gain ratio and weight gain. The nutrient and mineral utilization analysis showed significant variation (P< 0.05) in the percent nitrogen and energy retention as well as calcium and phosphrous retention values among the diets. Birds fed diet 2 had their nitrogen retention improved (83.32%). The cost analysis indices showed significant (P< 0.05) differences. Diet 4 was the cheapest (N39.07) per kilogramme while diet 1 gave the least marginal revenue (N451.34). From the foregoing, the Danish fishmeal, crayfish dust meal and shrimp waste meal are generally comparable and had no adverse effect on the performance and economic of broiler production through the combination of crayfish dust meal and shrimp waste meal proved to be the best diet. This is an indication that satisfactory animal protein can be prepared from these unconventional sources.